2019
DOI: 10.4067/s0034-98872019000700870
|View full text |Cite
|
Sign up to set email alerts
|

Fragilidad y su correlación con calidad de vida y utilización de los servicios de salud en personas mayores que viven en la comunidad

Abstract: Quality of life among frail older people Background: Frailty has a great impact in the wellbeing of older people. Aim: To evaluate the quality of life of older people with and without frailty. Material and Methods: We assessed sociodemographic variables, health, integral geriatric assessment, quality of life using the WHOQoL-BREF questionnaire and the level of fragility using the Tilburg Frailty Indicator (TFI) in 538 participants. Results: Three hundred and five participants aged 73 ± 7 years (229 women) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
1
7
0
2
Order By: Relevance
“…There are no studies prior to ours that investigate these two variables with the same assessment instruments. Even so, these results corroborate studies that used other instruments such as the Edmonton Frailty Scale (EFE), Whoqol-Bref and Whoqol-old (16) ; Tilburg Frailty Indicator (TFI) and Whoqol-Bref (4) ; Comprehensive Frailty Assessment Instrument (CFAI) and Whoqol-Bref (19) in addition to TFI and Whoqol-old (20) . This evidence reinforces that, regardless of the instrument used, frailty is always associated with reduced QoL in old age, found once again in this study, in which significant and negative coefficients were evidenced for all the tested relationships between frailty and QoL, with except for the weight loss component, which had no statistical significance.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…There are no studies prior to ours that investigate these two variables with the same assessment instruments. Even so, these results corroborate studies that used other instruments such as the Edmonton Frailty Scale (EFE), Whoqol-Bref and Whoqol-old (16) ; Tilburg Frailty Indicator (TFI) and Whoqol-Bref (4) ; Comprehensive Frailty Assessment Instrument (CFAI) and Whoqol-Bref (19) in addition to TFI and Whoqol-old (20) . This evidence reinforces that, regardless of the instrument used, frailty is always associated with reduced QoL in old age, found once again in this study, in which significant and negative coefficients were evidenced for all the tested relationships between frailty and QoL, with except for the weight loss component, which had no statistical significance.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, a study (4) developed in Chile used the TFI instruments to assess frailty and the Whoqol-Bref to assess the QoL of 538 older adults, in which it was identified that frailty was associated with a lower QoL of participants and worse scores in various assessment instruments in geriatrics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As stated, the findings show that the impacts of sociodemographic characteristics on HRQoL in older adults tend to be similar in the East and West. These findings will also provide evidence that can be used to develop tailored measures for elderly Koreans who are vulnerable to low HRQoL [30].…”
Section: Discussionmentioning
confidence: 85%